A preliminary fish survey of the estuaries on the south-east coast of South Africa, Kei Estuary to Mdumbi: A comparative study - NC James; TD Harrison (Water SA, 2020)
A preliminary ichthyofaunal and physico-chemical survey of estuaries on the south-east coast of South Africa from the Kei Estuary to the Mdumbi Estuary was undertaken between October and November 1997. Twenty-seven (27) estuaries were surveyed along this stretch of coastline and these were grouped into three estuary types: small (< 10 ha) predominantly closed estuaries, moderate to large (> 10 ha) predominantly closed estuaries and predominantly open estuaries. Multivariate analyses revealed significant differences between predominantly closed estuaries and predominantly open estuaries in terms of both their physico-chemical characteristics and their fish communities. There was no difference between small and moderate to large predominantly closed estuaries.  A significant relationship was also observed between the physico-chemical characteristics of the estuaries and their fish communities.  The estuaries in the study area fall within the warm-temperate biogeographic region; temperate species dominated the fish communities of all the estuaries. This survey represents one of the few fish surveys undertaken along this little-studied section of the coastline.